2014
DOI: 10.1007/s13760-014-0305-z
|View full text |Cite
|
Sign up to set email alerts
|

Dural puncture: an overlooked cause of cerebral venous thrombosis

Abstract: Cerebral venous thrombosis (CVT) accounts for 0.5-1 % of all strokes. Although dural puncture is proposed as one of the rare risk factors, this association has only been mentioned in anecdotal reports. Headache, i.e., usually the first and the most frequent clinical symptom on admission, is often attributed to the dural puncture itself. We investigated the frequency of CVT following a recent dural puncture in our stroke database, together with the other risk factors. The computerized medical records of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
1
9
0
1
Order By: Relevance
“…In our case, the development of CVT a week after dural puncture and symptoms, i.e. headache and seizures, are consistent with the published literature [8-9]. The exact mechanism is not known.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our case, the development of CVT a week after dural puncture and symptoms, i.e. headache and seizures, are consistent with the published literature [8-9]. The exact mechanism is not known.…”
Section: Discussionsupporting
confidence: 91%
“…Although the causal relationship could not be established, Guner at al. studied the frequency of cerebral venous thrombosis and dural puncture and found that 19.6% of patients who had a dural puncture in the previous seven days developed CVT [8]. In our case, the development of CVT a week after dural puncture and symptoms, i.e.…”
Section: Discussionmentioning
confidence: 53%
“…After lumbar puncture, if the headache is sustained or progressively aggravated or new symptoms appear, especially in patients with CVT susceptibility factors, the possibility of CVT should be considered. Guner et al ( 2015 ) conducted a retrospective study of 46 patients diagnosed with CVT. Of these, 19.6% (9 cases) had a lumbar history before onset.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…9 10 Importantly, all patients in the study by Guner et al had an additional predisposing risk factor for CVT including inherited thrombophilia or malignancy. 9 The pathogenesis of CVT after a dural puncture is poorly understood. Several mechanisms have been proposed including damage to venous endothelium due to stretch from negative spinal-cranial pressure, decreased venous velocity and reduced absorption of CSF in the sinuses.…”
Section: Discussionmentioning
confidence: 99%